NBD-Based Environment-Sensitive Fluorescent Probes for the Human Ether-a-Go-Go–Related Gene Potassium Channel - Li, Qi; Chai, Lijuan; Dong, Gaopan; Zhang, Xiaomeng; Du, Lupei (Frontiers in Molecular Biosciences, 2021)
Three environment-sensitive probes were developed for hERG channel based on the nitrobenzoxadiazole (NBD) fluorophore herein. After careful evaluation, probes M1 and M3 have a high affinity for imaging hERG channel in the cell-based experiment. Compared with other fluorescent labeling technologies (such as fluorescent proteins), these probes afford a convenient and economical method to determine hERG channel in vitro and in cellulo. Therefore, these probes are expected to apply for physiological and pathological studies of hERG channels and have the potential to establish a screening system for hERG channels.